DEVELOPMENT OF ORGANIC PRODUCTION IN UKRAINE - DANIUK, Yurii; LYNCHAK, Nadiia; KOVALCHUK, Yevheniia; BARBAN, Olha; TAGANTSOVA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines current trends in the global organic market, determines Ukraine’s place on it, characterizes the production of organic agricultural products in our country with an emphasis on the correct choice of varieties for key crops. Organic lands occupy 2% of all agricultural land in the world. More than 2/3 of them are formed by permanent pastures, and usually among the popular types of crops are cereals, oilseeds, legumes, nuts, coffee, olives, vegetables. The result of the constant development of the global organic market is an increase in such specialized lands to almost 100 million hectares and the number of producers to 4.3 million in 2023. The organic sector is growing rapidly due to the constant rise of demand for its products, stimulating the improvement of cultivation technologies. Our country has been developing organic agriculture since the late 1990s. We are ranked 22nd in the world in terms of total organic areas, while we are on the third place in the oilseed segment. As a result of the full-scale war, the Ukrainian organic sector lost approximately 35–40% of its potential, although according to the results of 2024 it managed to return to the top three suppliers to markets of the European Union countries. In contrast to exports, the domestic market is very poorly developed due to practically unformed consumer demand. According to the latest available data, there are 383 organic producers and 70 processors in Ukraine. The optimal list of varieties for growing determined different fruit and agricultural crops in our country, which can be sold on foreign markets, is considered. The indicators and reasons for lower yields in organic production compared to traditional production are characterized using the example of soybeans. The significantly lower energy consumption and harmful emissions in organic crop production are described. An assessment the prospects of Ukrainian and world organic sector of agriculture is given, taking into account the current situation of the global market.